PERBANDINGAN LEMBAGA EKSEKUTIF DI INDONESIA DAN KOREA SELATAN: A Comparison of Executive Institutions in Indonesia and South Korea - Aley Zaenal Gozali; Ninuk Wijiningsih (Faculty of Law, Trisakti University, 2024)
Indonesia and South Korea are contries that implement a presidential system where there is a separation of powers, namely the executive, legislative, and Judiciary based on the principle “Checks and Balances”. This principle is reflected in the 1945 constitution of the Republik of Indonesia and the constitutions of the Republic of Indonesia and Sound Korea. The formulation of the problem in this study is The similarities and differences of executive institutions in Indonesia and South Korea? What are the advantages and disadvantages of executive institution in Indonesia and South Korea?. This study uses normative research, which is descriptive sourced from secondary data and primary data, using deductive logic conclusions. The result research and conclusions of this study is, 1) Executive institutions in principle Indonesia and South Korea have many similarities in function, dutties and authorities. The difference can be observed in the terms used for the president’s companion. In Indonesia , the presidencial candidate is referres to as the vice president is accompanied bt yhe prime minister. 2) In general, executive institutions in Indonesia and South Korea still leave shortcomings, namely, conflicts between the executive and legislature tend to be possible given the absence of high state institutions that ultimately make decisions on policies seem long, due to check and balance.